Reconceptualizing Sight Words: Building an Early Reading Vocabulary. (4th December 2018) - Rawlins, Amanda; Invernizzi, Marcia
Abstract: Sight word learning occurs in most early elementary classrooms. Some kindergarten students face the prospect of learning up to 100 sight words, and many teachers feel pressure to ensure that students know lists of words by the year's end. The authors offer five assertions about sight word learning to direct teachers and administrators toward the research behind word learning and building an early reading vocabulary. The discussion includes how we learn words, how teachers can choose words for early readers, how teachers can ensure that the words stick, and how teachers can choose instructional activities around sight word learning.